(untitled) (International Journal of Agricultural Extension and Education, 2025)
The present study intended to identify the learning style of pre-service teachers and to analyse the learning styles of pre-service teachers considering their population variables such as gender, subject specialization and region which they belong. The study was carried out with 329 pre-service teachers who currently doing their bachelor of education programme at various places of Tamilnadu and Telangana. To analyse the preferred learning style of the pre-service teachers VAK inventory which is developed and standardized by Dhanya Krishnan in the year 2011 was used. The findings of the present study reveal that visual learning is the most preferred learning style which is followed by auditory and kinesthetics. Furthermore, there were slight difference in learning style based on gender, subject specialization and region, but it was a moderate difference. However, there are variation across different learning style, highlighting the need for a mixed approach that integrates visual, auditory and kinesthetics methods. This will ensure that all the students, regardless of their preferred learning style, can learn effectively based on their strengths.